Specific insulin and proinsulin secretion in glucokinase-deficient individuals - Pardini,V.C. (1999)
Glucokinase (GCK) is an enzyme that regulates insulin secretion, keeping glucose levels within a narrow range. Mutations in the glucokinase gene cause a rare form of diabetes called maturity-onset diabetes of the young (MODY). An early onset (less than 25 years), autosomal dominant inheritance and low insulin secretion stimulated by glucose characterize MODY patients. Specific insulin and proinsulin were measured in serum by immunofluorimetric assays (IFMA) during a 75-g oral glucose tolerance test (OGTT). Two kindreds (SA and LZ) were studied and compared to non-diabetic unrelated individuals (control group 1) matched for age and body mass index (BMI). In one kindred, some of these subjects were also obese (BMI >26 kg/m2), and other family members also presented with obesity and/or late-onset NIDDM. The MODY patients were also compared to a group of five of their first-degree relatives with obesity and/or late-onset NIDDM. The proinsulin profile was different in members of the two MODY kindreds. Fasting proinsulin and the proinsulin/insulin ratio were similar in MODY members of kindred LZ and subjects from control group 1, but were significantly lower than in MODY members of kindred SA (P<0.02 and P<0.01, for proinsulin and proinsulin/insulin ratio, respectively). Moreover, MODY members of family SA had higher levels of proinsulin and proinsulin/insulin ratio, although not significantly different, when compared to their first-degree relatives and to subjects from control group 2. In conclusion, we observed variable degrees of proinsulin levels and proinsulin/insulin ratio in MODY members of two different kindreds. The higher values of these parameters found in MODY and non-MODY members of kindred SA is probably related to the obesity and late-onset NIDDM background present in this family.